The Significant of Cobit Mapping Business Goal 12 and IT Goal 19 (Case Study: Stikom Surabaya) - Siti Mukaromah; Apol Pribadi Subriadi (IPTEK Journal of Proceedings Series, 2015)
IT Governance is a branch of the corporate governance system focused on information technology (IT) as well as performance and risk management. IT Governance is defined as the processes that ensure the effective and efficient use of IT in enabling an organization to achieve its goal. There are many different frameworks that can be used for managing the delivery of cost-effective IT services. IT managing the delivery of cost-effective IT services does not always give the advantage to the company. There are times when the IT managing the delivery of cost-effective IT services does not provide any benefit, it can cause IT Productivity Paradox. IT Productivity Paradox can be prevented, one is to analyze the processes undertaken with IT. From this analysis we will get the significance of the relationship processes with the IT Goal. The significance will be seen which one significant process and which one are not significant to the IT Goal. If the IT process there are not significant to the IT Goal, the process does not need to be repaired because it has no effect on IT Goal. Existing IT governance frameworks are COBIT, ITIL, ISO 20000, 17799/27001, Six Sigma, etc. The IT Infrastructure Library (ITIL), initially developed in the UK by the Office of Government Commerce (OGC), is gaining traction in the global IT community as a framework for IT governance. ISO 20000-focusing upon IT service management. ISO 17799 / ISO 27001 - focusing upon information. Six Sigma-focusing upon operational performance and defect identification. COBIT - framework for information IT management risks. Control Objectives for Information and related Technology (COBIT) provides good practices across a domain and process framework and presents activities in a manageable and logical structure. COBIT’s good practices represent the consensus of experts. They are strongly focused more on control, less on execution. These practices will help optimise IT-enabled investments, ensure service delivery and provide a measure against which to judge when things do go wrong. This research is intend to find out whether Cobit mapping Business Goal to IT Goal appropriate with case study. The result The results using SEM approach shows that the mapping of COBIT is not significant in the case studies of academic administration.